2012
DOI: 10.1111/j.1875-595x.2011.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental composite fillings and bisphenol A among children: a survey in South Korea

Abstract: Having many dental composite filling surfaces on teeth may increase the urinary BPA concentration in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The inverse association between BPA in a child's urine and the presence of white dental fillings, confirmed by the statistical model, is confusing, since BPA can be present as an impurity in the polymers used in fillings, which can then leach out as a result of hydrolysis through esterases present in saliva (Geens et al, 2012). Elevated BPA associated with presence of dental fillings has been shown by different in vitro, in vivo (Geens et al, 2012) and population-based studies in children (Chung et al, 2012). On the basis of in vivo studies, the highest exposures were measured immediately after sealant placement (Fleisch et al, 2010), and there is evidence that the released BPA depends on the producer of the dental resins/sealants (Fleisch et al, 2010;Joskow et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The inverse association between BPA in a child's urine and the presence of white dental fillings, confirmed by the statistical model, is confusing, since BPA can be present as an impurity in the polymers used in fillings, which can then leach out as a result of hydrolysis through esterases present in saliva (Geens et al, 2012). Elevated BPA associated with presence of dental fillings has been shown by different in vitro, in vivo (Geens et al, 2012) and population-based studies in children (Chung et al, 2012). On the basis of in vivo studies, the highest exposures were measured immediately after sealant placement (Fleisch et al, 2010), and there is evidence that the released BPA depends on the producer of the dental resins/sealants (Fleisch et al, 2010;Joskow et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…In a study of 20 children, urinary BPA levels increased after dental composite treatment and had not returned to baseline levels at the end of follow-up two weeks later (Martin et al, 2005). A cross-sectional study in South Korean children found significantly higher urinary BPA levels (2.67 μg/g creatinine) in children with more than ten composites and sealants than those with no fillings (Chung et al, 2012). However, causality cannot be determined in these observational studies, particularly considering the numerous possible exposure routes of BPA in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the number of RBSs and RBC restorations present in their oral cavity, the children were classified into four groups. The group of children with more than 11 sealants/restorations showed a BPA urine concentration level of 9.13 µg/g, which was much higher than the control group [60].…”
Section: Release From Resin Fissure Sealantsmentioning
confidence: 65%
“…Chung et al, obtained urine samples from 495 children aged between 8 to 9 years [60]. The medium creatinine-adjusted urinary BPA level was 2.08 ± 3.81 μg⁄g.…”
Section: Release Into Urinementioning
confidence: 99%